RNA-Based Antipsoriatic Gene Therapy: An Updated Review Focusing on Evidence from Animal Models - Lin ZC; Hung CF; Aljuffali IA; Lin MH; Fang JY (Dove Medical Press, 2024)
Zih-Chan Lin,1 Chi-Feng Hung,2- 4 Ibrahim A Aljuffali,5 Ming-Hsien Lin,6 Jia-You Fang7- 9 1Chronic Diseases and Health Promotion Research Center, Chang Gung University of Science and Technology, Puzi, Chiayi, Taiwan; 2School of Medicine, Fu Jen Catholic University, New Taipei City, Taiwan; 3Program in Pharmaceutical Biotechnology, Fu Jen Catholic University, New Taipei City, Taiwan; 4School of Pharmacy, Kaohsiung Medical University, Kaohsiung, Taiwan; 5Department of Pharmaceutics, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 6Department of Dermatology, Chi Mei Medical Center, Tainan, Taiwan; 7Pharmaceutics Laboratory, Graduate Institute of Natural Products, Chang Gung University, Kweishan, Taoyuan, Taiwan; 8Research Center for Food and Cosmetic Safety and Research Center for Chinese Herbal Medicine, Chang Gung University of Science and Technology, Kweishan, Taoyuan, Taiwan; 9Department of Anesthesiology, Chang Gung Memorial Hospital, Kweishan, Taoyuan, TaiwanCorrespondence: Ming-Hsien Lin, Department of Dermatology, Chi Mei Medical Center, 901 Zhonghua Road, Yongkang, Tainan, Taiwan, Email i5483123@nckualumni.org.tw Jia-You Fang, Pharmaceutics Laboratory, Graduate Institute of Natural Products, Chang Gung University, 259 Wen-Hwa 1st Road, Kweishan, Taoyuan, 333, Taiwan, Email fajy@mail.cgu.edu.twAbstract: Psoriasis presents as a complex genetic skin disorder, characterized by the interaction between infiltrated immune cells and keratinocytes. Substantial progress has been made in understanding the molecular mechanisms of both coding and non-coding genes, which has positively impacted clinical treatment approaches. Despite extensive research into the genetic aspects of psoriasis pathogenesis, fully grasping its epigenetic component remains a challenging endeavor. In response to the pressing demand for innovative treatments to alleviate inflammatory skin disorders, various novel strategies are under consideration. These include gene therapy employing antisense nucleotides, silencing RNA complexes, stem cell therapy, and antibody-based therapy. There is a pressing requirement for a psoriasis-like animal model that replicates human psoriasis to facilitate early preclinical evaluations of these novel treatments. The authors conduct a comprehensive review of various gene therapy in different psoriasis-like animal models utilized in psoriasis research. The animals included in the list underwent skin treatments such as imiquimod application, as well as genetic and biologic injections, and the results of these interventions are detailed. Animal models play a crucial role in translating drug discoveries from the laboratory to clinical practice, and these models aid in improving the reproducibility and clinical applicability of preclinical data. Numerous animal models with characteristics similar to those of human psoriasis have proven to be useful in understanding the development of psoriasis. In this review, the article focuses on RNA-based gene therapy exploration in different types of psoriasis-like animal models to improve the treatment of psoriasis.Keywords: psoriasis, animal model, gene therapy, siRNA, miRNA